Interaction of ncRNA and Epigenetic Modifications in Gastric Cancer: Focus on Histone Modification - Yang, Qingfan; Chen, Yu; Guo, Rui; Dai, Yalan; Tang, Liyao; Zhao, Yueshui; Wu, Xu; Li, Mingxing; Du, Fukuan; Shen, Jing; Yi, Tao; Xiao, Zhangang; et al. (Frontiers in Oncology, 2022)
Gastric cancer has developed as a very common gastrointestinal tumors, with recent effective advancements in the diagnosis and treatment of early gastric cancer. However, the prognosis for gastric cancer remains poor. As a result, there is in sore need of better understanding the mechanisms of gastric cancer development and progression to improve existing diagnostic and treatment options. In recent years, epigenetics has been recognized as an important contributor on tumor progression. Epigenetic changes in cancer include chromatin remodeling, DNA methylation and histone modifications. An increasing number of studies demonstrated that noncoding RNAs (ncRNAs) are associated with epigenetic changes in gastric cancer. Herein, we describe the molecular interactions of histone modifications and ncRNAs in epigenetics. We focus on ncRNA-mediated histone modifications of gene expression associated with tumorigenesis and progression in gastric cancer. This molecular mechanism will contribute to our deeper understanding of gastric carcinogenesis and progression, thus providing innovations in gastric cancer diagnosis and treatment strategies.